2010
DOI: 10.1017/s0956536110000106
|View full text |Cite
|
Sign up to set email alerts
|

Onset of the Early Classic Period in the Southern Maya Lowlands: New Evidence From Punta De Chimino, Guatemala

Abstract: Desecration of Punta de Chimino's ceremonial precinct around a.d. 430 was associated with the appearance of green Pachuca obsidian, pyrite mirror fragments, dart points, a Tikal-style vessel cache, and a peculiar grave with Mexican semblances. A structurally housed Protoclassic stela was removed in an apparent fire ritual and monumental masks adorning the E-Group range building were effaced in a termination rite involving large quantities of refuse. Disuse of the E-Group range building and unfinished refurbish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The Early Classic material shows strong outside influences and multiple ties to the central Peten, which corresponds with the close ties noted by Bachand (2006, 2010) at Punta de Chimino beginning in a.d. 430. The iconographic data in particular show interactions with the Tikal sphere, which corroborates data from Carot (1989) in the Candelaria system and Ichon and Arnauld (1985) in La Lagunita.…”
Section: New Insights Into the Early History Of The Great Western Trasupporting
confidence: 79%
See 3 more Smart Citations
“…The Early Classic material shows strong outside influences and multiple ties to the central Peten, which corresponds with the close ties noted by Bachand (2006, 2010) at Punta de Chimino beginning in a.d. 430. The iconographic data in particular show interactions with the Tikal sphere, which corroborates data from Carot (1989) in the Candelaria system and Ichon and Arnauld (1985) in La Lagunita.…”
Section: New Insights Into the Early History Of The Great Western Trasupporting
confidence: 79%
“…The Petexbatun material did not necessarily fall into the same chronological pitfalls, since the majority of investigations were limited to the Late and Terminal Classic periods in order to investigate the causes of the Classic Maya collapse. More recent research (Bachand 2006, 2010; Eberl 2007; Escobedo 1997) in the Petexbatun region has demonstrated the existence of a local dynasty (referred to as the “Scroll Dynasty” by Houston [1993] and Eberl [2007]) that existed at the sites of Tamarindito and Arroyo de Piedra. Petexbatun residents were involved in interregional trade—directly or indirectly—with other areas beyond the Maya world, as evinced by the presence of Mexican obsidian from at least two sources from fill at Punta de Chimino (Aoyama 2009; Eberl 2007).…”
Section: Previous Investigations In the Preclassic Period And Early Cmentioning
confidence: 99%
See 2 more Smart Citations
“…These sequential platform renovations, however, created more restricted access to the temple precinct and ceremonies that took place in Caobal's main plaza. This pattern of restricted ceremonial space is repeated at a number of Pasión centers around this time (Bachand 2010;Johnston 2006;Smith 1972) albeit in variant architectural forms. The dedicatory burial practices associated with Caobal's renovated temple platform further imply new expressions of corporeal, as opposed to supernatural, power.…”
Section: Creating Community Through Repeated Practicementioning
confidence: 98%